Relevance of Partitioning DLCO to Detect Pulmonary Hypertension in Systemic Sclerosis - Sivova, Nadia (Public Library of Science, 2013)
We investigated whether partitioning DLCO into membrane conductance for CO (DmCO) and pulmonary capillary blood volume (Vcap) was helpful in suspecting precapillary pulmonary (arterial) hypertension (P(A)H) in systemic sclerosis (SSc) patients with or without interstitial lung disease (ILD). We included 63 SSc patients with isolated PAH (n=6), isolated ILD (n=19), association of both (n=12) or without PAH and ILD (n=26). Partitioning of DLCO was performed by the combined DLNO/DLCO method. DLCO, DmCO and Vcap were equally reduced in patients with isolated PAH and patients with isolated ILD but Vcap/alveolar volume (VA) ratio was significantly lower in the isolated PAH group. In patients without ILD, DLCO, DmCO, Vcap and Vcap/VA ratio were reduced in patients with isolated PAH when compared to patients without PAH and both Vcap/VA and DLCO had the highest AUC to detect PAH. In patients with ILD, Vcap had the highest AUC and performed better than DLCO to detect PH in this subgroup. In conclusion, Vcap/VA was lower in PAH than in ILD in SSC whereas DLCO was not different. Vcap/VA ratio and DLCO had similar high performance to detect PAH in patients without ILD. Vcap had better AUC than DLCO, DmCO and FVC/DLCO ratio to detect PH in SSC patients with ILD. These results suggest that partitioning of DLCO might be of interest to detect P(A)H in SSC patients with or without ILD.